2021
DOI: 10.1007/s00259-021-05215-4
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG brain PET hypometabolism in patients with long COVID

Abstract: Purpose In the context of the worldwide outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), some patients report functional complaints after apparent recovery from COVID-19. This clinical presentation has been referred as "long COVID." We here present a retrospective analysis of 18 F-FDG brain PET of long COVID patients from the same center with a biologically confirmed diagnosis of SARS-CoV-2 infection and persistent functional complaints at least 3 weeks after the initial infection. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
318
4
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(368 citation statements)
references
References 29 publications
25
318
4
21
Order By: Relevance
“…The Covid-19 pandemic has caused significant morbidity and mortality throughout the world, as well as major social and economic disruptions. In the field of nuclear medicine, some exciting imaging findings associated with Covid-19 were described [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic has caused significant morbidity and mortality throughout the world, as well as major social and economic disruptions. In the field of nuclear medicine, some exciting imaging findings associated with Covid-19 were described [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is known that astrocytes play pivotal roles in the brain defence against peripheral inflammatory changes [11]. Guedj and colleagues [1] mentioned that acute systemic inflammation and SARS-CoV-2 neurotropism could be related to brain inflammatory alterations. Complementary, other groups identified signs of reactive astrogliosis in postmortem tissue of COVID-19 patients [12], in cellular models and in brain organoids [13].…”
Section: Cellular Origins Of 18 F-fdg Pet Hypometabolism In Covid-19mentioning
confidence: 99%
“…While the cellular origins of brain 1 8 F-FDG PET hypometabolism in COVID-19 remain to be defined, it seems clear that we are dealing with persistent synaptic dysfunction. Guedj et al [1] demonstrated that multiple brain regions are hypometabolic in long COVID. In addition, it seems that there is a link between clinical manifestations and regional glucose hypometabolism.…”
Section: Persistent Brain Hypometabolism Measured By 18 F-fdg Pet -A Risk For Developing Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…136 One study comparing 35 Long COVID patients to 44 controls found significant hypometabolism in the brain, including the olfactory gyrus, right temporal lobe (including the hippocampus and amygdala), the bilateral pons/medulla brainstem, and the bilateral cerebellum; notably, the clusters of hypometabolism were correlated with patient symptoms, including hyposmia and anosmia, memory and cognitive impairment, pain, and insomnia. 137 There have also been additional suggestions that brainstem dysfunction might be involved in a variety of COVID-19 clinical manifestations. For instance, Yong 138 cites a number of autopsy studies to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%